PENGARUH CAR DAN LDR TERHADAP HARGA SAHAM PADA PT BANK CENTAL ASIA TBK - Hatimah, Husnul; Nurulrahmatia, Nafisah; Muniarty, Puji (Cattleya Darmaya Fortuna, 2024)
This research was conducted with the aim of testing the effect of capital adequacy ratio, loan to deposit ratio on share prices at PT. Bank Central Asia Tbk is listed on the Indonesian Stock Exchange (BEI) for the period 2000-2022. The data used in this research is based on quantitative data. The research instrument used to measure this research uses data on total credit, third party funds, total capital, ATMR and share prices originating from the balance sheet financial report at PT. Bank Central Asia Tbk. The population of this research is the financial statements of PT. Bank Central Asia Tbk for 18 years, namely from 2005-2022. The sample in this research is the financial report of PT. Bank Central Asia Tbk for 10 years, namely 2013-2022. The sampling technique used in this research was purposive sampling. The data collection techniques used in this research are documentation and literature study. The data analysis technique in this research uses the classical assumption test, multiple linear regression test, t test, f test using the SPSS 24 program. The results of the study show that the capital adequacy ratio variable has a partial effect on stock prices, while the loan to deposit ratio variable has no effect. partially on share prices. Simultaneously, the capital adequacy ratio and loan to deposit ratio variables influence stock prices.